PENGHAPUSAN DISKRIMINASI TERHADAP ANAK ASTRA DALAM PERSPEKTIF PERLINDUNGAN ANAK - Ni Ketut Sri Ratmini (VYAVAHARA DUTA, 2021)
This study focuses on eliminating discrimination against Astra children from the perspective of child protection. There are two main issues discussed in this study, namely: (1) what are the forms of discrimination against Astra children? and (2) how to eliminate discrimination against Astra's children from the perspective of child protection.This research is a normative juridical law research, using a statutory approach. The results of this study are: the form of discrimination against Astra children is not being able to use the clan name of their biological father to not having rights as heirs. Elimination of discrimination against Astra's children from the perspective of child protection can be carried out in three ways, namely, one by giving recognition to Astra's children from their biological fathers, two by giving rights to children as mandated by law, three by assigning Astra children as adopted children.